Transformation of Covalent Organic Frameworks from N‐Acylhydrazone to Oxadiazole Linkages for Smooth Electron Transfer in Photocatalysis. (12th January 2022) - Yang, Shuailong; Lv, Haowei; Zhong, Hong; Yuan, Daqiang; Wang, Xinchen; Wang, Ruihu
Abstract: Covalent organic frameworks (COFs) are regarded as new platforms for solar‐to‐chemical energy conversion due to their tailor‐made functions and pre‐designable structures. Their intrinsic reversibility and the high polarization of organic linkages inevitably result in poor chemical stability and weak optoelectronic properties. Herein, one N ‐acylhydrazone‐linked COF (H‐COF) was converted into a stable and π‐conjugated oxadiazole‐linked COF via post‐oxidative cyclization. Both chemical stability and π‐electron delocalization throughout the reticular framework are significantly improved, leading to a high hydrogen evolution rate of 2615 μmol g −1 h −1 upon visible light irradiation, which is over four times higher than that of H‐COF. This work provides a facile protocol for the fabrication of π‐conjugated COFs and the modulation of photophysical properties for photocatalytic application. Abstract : Oxadiazole‐linked covalent organic framework has been constructed through oxidative cyclization of N ‐acylhydrazone linkage. Both chemical stability and π‐electron delocalization are significantly improved, thus upgrading photocatalytic hydrogen generation. This work provides facile protocols for the modulation of photophysical properties for photocatalysis.